Pengaruh Model Pembelajaran Inkuiri terbimbing disertai LKPD berbasis Multi Representasi terhadap Aktivitas Belajar dan HOTS siswa SMP kelas VIII - Leny Nurfalina; Sri Wahyuni; Ulin Nuha (ScienceEdu, 2024)
The purpose of this research is to study the influence of implementing the guided inquiry learning model accompanied by multi-representation-based LKPD on substance stress material on the learning activities and HOTS of class VIII junior high school students. This research used a sample of class VIII A as the experimental class and class VIII B as the control class. Data collection techniques include pre-test and post-test written tests, LKPD, observation, interviews and documentation. The results of data analysis using the HOTS independent sample t-test and learning activities show a sig. 2 (tailed) < 0.05, which means that the experimental class score is higher than the control class. So it can be concluded that learning using the guided inquiry learning model accompanied by multi-representation based LKPD has a significant effect on the activities and HOTS of junior high school students.